A PRACTICAL MULTIPLE-TOOL-SET APPROACH FOR INCREASING AGILE RESPONSE IN OVERHAUL PRODUCTION WITH LIMITED RESOURCE REQUIREMENT VISIBILITY - Chou, Han-Hsin; Wang, Chi-Tai; Sheu, Ru-Shuo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
Agility has become a manufacturing paradigm of the 21st century that numerous firms have adopted it as a competitive strategy. Not surprisingly, there is a comprehensive body of research conducted on this subject. However, little study has been done for one-of-a-kind manufacturing where resource requirements are not available until well into the manufacturing process. In addition, there are other uncertain factors such as the changing production lead-time, making the environment dynamic and hard to predict. To address this issue, we conduct an action research study to enable an agile response to the factory dynamics of the subject environment. Our solution is a novel integration of four widely used technologies: radio frequency identification (RFID), simulation, bottleneck identification methods and the theory of constraints (TOC). Using numerical industry data, we illustrate how this multiple-tool-set approach is effective in achieving agility in a real one-of-a-kind manufacturing facility. With minor modifications, our solution can also be used in other manufacturing environments.